PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DI LAHAN GAMBUT YANG DIBERI AMELIORAN DAN PUPUK NITROGEN - Rohmololo riana bancin; Murniati '; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objective of research was to know the growth and production of onion  after giving of ameliorant and nitrogene fertilizer. The research was done in experimentation area Faculty of Agroteknologi Universitas Riau, Rimbo Panjang village, subdistric Tambang, Kampar from March to May 2015. The research was using the Randomized Block Design Factorial with two factors. The first factor amelioran with five levels namely control (A0), dolomite 1,5 ton/ha (A1), calcite 2 ton/ha, oil palm bunch ash 5 ton/ha (A3) and  rice husk ash 15 ton/ha (A4).  The second factor  of nitrogene fertilizer with three levels namely control (N0), urea fertilizer 500 kg/ha (N1) and ZA fertilizer 1095 kg/ha (N2). Parameter observed were plant height, total of leaves, total tuber, rim tuber, fresh weight tuber per plot and dry weight tuber per plot. The result of the research showed that the ameliorant application was significant of rim tuber, fresh weight tuber/plot, and reasonable save tuber weight/plot, but not significant wet the plant height, total of leaves, total tuber. Nitrogene fertilizer showed significant on fresh weight tuber per plot, and dry weight per plot, but not significant the plant height, total of leaves, rim tuber, total tuber. The interaction between ameliorant and nitrogene fertilizer showed that no significant for all parameters. showed significant on fresh weight tuber per plot and dry weight tuber per plot, but no significant the plant height, total of leaves, rim tuber, total tuber.   Keyword : Onion, peat soil, ameliorant and nitrogene fertilizer.